The Traction Calculation Simulation System for Straddle-type Monorail Car - 杜子学; 杨林; 文孝霞 (机车电传动)
This paper realized the design and development of traction calculation system for straddle-type monorail car by using objectoriented programming software-Visual Basic 2005, which was on the base of the line’s profile and straddle-type monorail car’s data of the No.2 light rail line of Chongqing. The test results indicate that the system can be used easily with accurate results, which can be used as a reference for traction calculation for straddle-type monorail car’s traction calculation.